Estudo fitoquímico de Sidastrum paniculatum (L.) Fryxell e síntese de amidas análogas às isoladas da família Mavaceae - Marques, Sany Delany Nunes (2018)
Sidastrum paniculatum (L.) Fryxell, a species belonging to the family Malvaceae, is popularly known as "malva roxa" or "malvavisco". The present work was to increase the knowledge about the phytochemicals of S. paniculatum through a phytochemical study to isolate their polar substances and synthesis reactions to prepare analogous amides for those isolated from Malvaceae species. For the isolation and analysis of the chemical constituents were adopted chromatographic methods such as column chromatography and flat chromatography. In order to synthesize amides, MBH (Morita-Baylis-Hillman) adducts were used as substrates for the synthesis of these molecules, having as starting reagents aromatic aldehydes and commercial amines, in a synthesis that follows from 3-5 reactional steps. This study reports the isolation and identification of 10 substances: stearic acid (Sp-1), N-trans-feruloylthyramine (Sp-2), acacetin (Sp-3), apigenin, 7,4'-di-O-methyl-7-O-sulphate isoscutellarein (Sp-6); yannin (Sp-7), beltraonin (Sp-8a), and two new sulfated flavonoids: 7-O-sulphate isoscutellarein (paniculatumin) (Sp-8b) in admixture with Sp-8a, and 7,4'-O-dimethyl-8-O-sulfate hypoaletin (sidastrumin) (Sp-9). The sulfated flavonoids were subjected to molecular studies on the Aedes aegypti target proteins (Aedes aegypti kynurenine aminotransferase and Sterol Carrier Protein2), where the Sp-6 and Sp-8a flavonoids had the potentiality to interact with both target proteins, these being the most indicated to be studied in vitro. This study also reports the synthesis of 40 molecules, 20 amides, of which 18 are unprecedented in the literature, from reactions with a mean yield of 82%. The compounds had their chemical structures determined and identified by analysis of the NMR (1H, 13C, HMQC, HMBC and COSY), TOFMS, infrared, polarization spectra and comparisons with literature data. Among the compounds synthesized 2d and 2b adducts, 7c acid and 4g, 4h and 8e amides were evaluated for antifungal activity, where the adducts and acid showed activity against yeast fungi including C. albicans, C. tropicalis and C. krusei and the amides showed a lower profile of antifungal activity, with inhibition promoted only by 4g and 4h amides against few strains, while amide 8e was inactive.